Application of a Novel Design for Air Lift Reactor In Waste Water Treatment - Najmuldeen, Ghazi Faisal; Al Ezzi, Ali Abdul Rahman (IJSRSET, 2015)
The objective of this study is to design different treatment technologies to identify cost effective and technically feasible alternatives for the removal of (MTBE) from drinking water experimental rig and bench-scale studies using granular activated carbon (GAC) and hydrogen peroxide (H2O2) were conducted to observe the treatability of MTBE in synthetic wastewater. An experimental rig was built up that consist of air lift loop reactor was constructed with draft tube of 9 cm diameter and 1.25 m in height extends vertically in the center of and 1.5 m height of outer rectangular Plexiglas box (29 x 15.5 cm) and the solid particles{granular activated carbon (GAC) } were put in the annulus and gas was spared through the inner draft tube using a multi hole pouros distributor whereas liquid flowed through the down comer and a stable circulating liquid flow is induced by the density difference between the aerated liquid in the draught tube and the annulus . The draft tube is constructed to be open at both ends and was fitted with three supports at the upper, medium and the lower end of the column so as to locate it in central position at any distance above the base . A mechanism is provide to maintain constant liquid level inside the reactor , the mechanism to maintain constant liquid level is a valve or a raised outlet tube raised to the level of the liquid present in the reactor. The adsorption , stripping and oxidation processes take place during the circulation of oxidized waste water through (GAC) bed in annulus and this step give more time to complete the stripping, oxidation and adsorption processes in high efficiency. The major finding suggests that the air flow rate at 7 L/min and a molar ratio of MTBE/H2O2 equal 20 over the synthetic wastewater caused a greater removal of MTBE. From experimental observations, 90% of MTBE removal from synthetic wastewater.